2017
DOI: 10.1159/000481315
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Macrovascular Invasion: Defining the Optimal Treatment Strategy

Abstract: Background: Tumoral macrovascular invasion (MVI) of hepatic and/or portal vein branches is a common phenomenon in hepatocellular carcinoma (HCC) and is associated with poorer prognosis when compared to HCC without MVI. Summary: Current international guidelines for the management of HCC recommend sorafenib as the only treatment option in case of MVI. Despite guideline recommendations, several alternative options have been tested to manage HCC with MVI: surgery, transarterial chemoembolization, external or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 47 publications
2
79
0
1
Order By: Relevance
“…Practice guidelines primarily recommend the use of sorafenib , which can lead to a modestly prolonged survival (8.1 vs. 4.9 months) . Other studies suggest the use of locoregional radiological treatments in patients with preserved liver function, and segmental or sub‐segmental portal invasion . TACE can be safe and effective, using super‐selective catheterization techniques, and resulting in a modest survival gain from 0 to 35% at 5 years .…”
Section: Discussionmentioning
confidence: 99%
“…Practice guidelines primarily recommend the use of sorafenib , which can lead to a modestly prolonged survival (8.1 vs. 4.9 months) . Other studies suggest the use of locoregional radiological treatments in patients with preserved liver function, and segmental or sub‐segmental portal invasion . TACE can be safe and effective, using super‐selective catheterization techniques, and resulting in a modest survival gain from 0 to 35% at 5 years .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies combining surgical resection and molecular targeted treatment have provided encouraging results and improved the outcomes for HCC patients. However, the prognosis for patients with unresectable advanced-stage HCC remains poor (6,7). Sorafenib was the only systemic drug available for treating advanced HCC until the recent approval of regorafenib, another multi-kinase inhibitor (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines often struggle to fit these cases in, leaving them in a "grey area". There is increasing evidence suggesting that alternative strategies to sorafenib might improve patients' survival advanced HCC with macrovascular invasion but lack of sufficient evidence [60]. A recent meta-analysis by Chen et al [61] revealed that the overall survival is higher in hepatectomy than in the TACE group, and that hepatectomy was superior over TACE in 1-year and 3-year, but not 5-year.…”
Section: Discussionmentioning
confidence: 99%